Clinical Perspective on Primary Angiitis of the Central Nervous System in Childhood (cPACNS) - Smitka, Martin; Bruck, Normi; Engellandt, Kay; Hahn, Gabriele; Knoefler, Ralf; von der Hagen, Maja (Frontiers in Pediatrics, 2020)
Non-arteriosclerotic arteriopathies have emerged as important underlying pathomechanism in pediatric arterial ischemic stroke (AIS). The pathogenesis and classification of cerebral arteriopathies in childhood is heterogeneous. Different classifications base on the i) anatomic site ii) the distribution and size of the affected vessel iii) the timecourse, e.g. transient versus progressive, monophasic versus recurrent iii) the putative pathogenesis iv) the MRI morphology of the vasculopathies. Inflammation affecting the cerebral vessels is increasingly recognized as common cause of pediatric AIS. Primary cerebral vasculitis or primary angiitis of the central nervous system (CNS) in childhood (cPACNS) is an important differential diagnosis in pediatric AIS. PACNS is a rare disorder and the pathogenesis is poorly understood so far. The current classification of cPACNS is based on the affected cerebral vessel size, the disease course and angiographic pattern. Two large subtypes are currently recognized comprising large and medium sized vessel CNS vasculitis referred to as angiography-positive (AP-cPACNS) and angiography-negative small vessel (AN-cPACNS). As the clinical manifestations of cPACNS are rather diverse precise diagnosis can be challenging for the treating pediatrician due to the lack of vital laboratory tests or imaging features. Initial misdiagnosis is common because of overlapping phenotypes and pediatric AIS mimics. As untreated cPACNS is associated with a high morbidity and mortality, timely diagnosis and induction of immunomodulatory and symptomatic therapy is essential. Survival and neurological outcome depend on early diagnosis and prompt therapy. PACNS in childhood differs in several aspects from primary cerebral angiitis in adults. The aim of this article is to give a brief comprehensive summary on pediatric primary cerebral vasculitis focusing on the clinical perspective regarding the classification, the putative pathogenesis, the disease course, the diagnostic tools and emerging treatment options. A modified terminology for clinical practice is discussed.